2021
DOI: 10.1126/sciadv.abe8591
|View full text |Cite
|
Sign up to set email alerts
|

The cryo-EM structure of an ERAD protein channel formed by tetrameric human Derlin-1

Abstract: Endoplasmic reticulum–associated degradation (ERAD) is a process directing misfolded proteins from the ER lumen and membrane to the degradation machinery in the cytosol. A key step in ERAD is the translocation of ER proteins to the cytosol. Derlins are essential for protein translocation in ERAD, but the mechanism remains unclear. Here, we solved the structure of human Derlin-1 by cryo–electron microscopy. The structure shows that Derlin-1 forms a homotetramer that encircles a large tunnel traversing the ER me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
0
30
1
Order By: Relevance
“…Recent cryoelectron microscopy (cryo-EM) work demonstrated that Derlin-1 forms a tetrameric channel, and this complex was predicted to allow a single-transmembrane helix to pass through its pore during retrotranslocation (Rao et al, 2021). We wanted to determine whether Derlin-1 was able to induce lipid thinning as a tetrameric complex.…”
Section: Derlin-1 Homologous Mutants Disrupt Erad Of Cftrmentioning
confidence: 99%
“…Recent cryoelectron microscopy (cryo-EM) work demonstrated that Derlin-1 forms a tetrameric channel, and this complex was predicted to allow a single-transmembrane helix to pass through its pore during retrotranslocation (Rao et al, 2021). We wanted to determine whether Derlin-1 was able to induce lipid thinning as a tetrameric complex.…”
Section: Derlin-1 Homologous Mutants Disrupt Erad Of Cftrmentioning
confidence: 99%
“…Moreover, biochemical analysis of Doa10 and the Asi complexes revealed that these entities are sufficient for the retrotranslocation of ERAD-C substrates and orphan complex subunits, respectively (Natarajan et al, 2020;Schmidt et al, 2020). In addition, the structure of human Derlin1 was recently published (Rao et al, 2021), which postulates an entirely different route to the retrotranslocation of luminal and TM substrates. Human Derlin-1 and -2 contain a p97 interaction motif at their C terminus, which can serve to recruit p97 directly and fuel retrotranslocation.…”
Section: Reviewmentioning
confidence: 99%
“…After recognition by BiP or other ER luminal proteins, Derlin-1 often is engaged for dislocation of proteins from the ER membrane. Derlin-1 is a multi-pass ER transmembrane protein that recently has been shown to be a homotetramer with a channel large enough to transfer a protein α-helix to the cytosol, i.e., to serve as a retrotranslocon [ 139 ]. Cytosolic E1 and E2 enzymes cooperate with ER transmembrane E3 ligases to ubiquitylate target proteins prior to recognition by adapters and VCP for delivery to the proteasome [ 124 ].…”
Section: Involvement Of P97 In Viral Manipulation Of Erad and Immunitymentioning
confidence: 99%